Bogs, birds, and berries in Belarus: the governance and management dynamics of wetland restoration in a state-centric, top-down context - Lucas Dawson (Resilience Alliance, 2021)
Wetlands are complex social-ecological systems, which provide both important habitat for species, and multiple tangible and intangible benefits for people. Sustaining long-term benefits through restoration, conservation, and sustainable use is often linked to integrative and adaptive approaches to wetlands management. Such approaches assume democratic ideals, and require multilevel, multisector, and multiactor participation in governance and management arrangements. How then can functional wetlands be restored and sustainably managed as social-ecological systems in strongly state-centric, top-down governance contexts, such as in former Soviet republics? Using three case studies of wetland restoration and management for ecosystem functionality, biodiversity conservation, and human livelihoods, we employ a complex systems approach to analyze key governance and management dynamics underpinning initiatives toward sustainable wetlands in Belarus. We identified five core processes, namely, planning, garnering stakeholder support, obtaining key inputs (financial, human, material, technological, fixed capital), implementing core activities, and integrating learning and knowledge cycles. Key constraints concerned institutional hierarchies, onerous regulations, "negativism," and financing difficulties. Strategies relating to perception management, risk mitigation, and learning are identified as key to enabling beneficial feedback loops relating to core processes. Although path-dependent societal dynamics of the Soviet era continue to influence wetland systems, combinations of social and ecological crises created windows of opportunity for active participation among nongovernmental actors. Major opportunities for enabling emergent management approaches included identification of confluences of interest amongst stakeholders, as well as the continued mutual integration of Belarus with the international community.